GREEN ACCOUNTING FOR SUSTAINABLE DEVELOPMENT: CASE STUDY OF INDONESIA’S MANUFACTURING SECTOR - Rifda Nabila (Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this study was to examine the influence of Green Accounting and Environmental Performance on Sustainable Development Goals (SDGs) with Environmental Disclosure as an intervening variable. The population in this study is aÂ manufacturing company listed on theÂ Indonesia Stock Exchange (IDX) and participated in PROPER in the year 2015-2019. The research sample is 27 companies, with purposive sampling method of data collection. Types of data used is secondary. The analysis data technique and hypothesis testing using SmartPLS software. The results showed that the Green Accounting significantly positive effect on Environmental Disclosure and Environmental Disclosure significantly positive effect on Sustainable Development Goals (SDGs). However, the test results showed that, Environmental Performance does not significantly positive effect on Environmental Disclosure and Environmental Disclosure is not able to mediate the effect of Green Accounting and Environmental Performance on Sustainable Development Goals (SDGs)